Relative dosimetry in small fields: Which detector to choose?. (September 2016) - Dufreneix, S.; Josset, S.; Bartolo, C. Di; Autret, D.
Abstract : Introduction: Small field dosimetry is a challenging area. Since no ideal detector exists, it is recommended that at least three different suitable types be used. However, only one set of measurement is used by the treatment planning system. Purpose: To compare several detectors and select the adequate one. Materials and methods: Profiles, percent-depth-dose and output factors were conducted on a Novalis TrueBeam STx in MLC shaped beams with a field size of 3, 2, 1 and 0.5 cm for three energies (6 MV, 6 MV FFF and 16 MV) as well as in circular cones of 15–4 mm diameter at 6 MV and 6 MV FFF. Depending on the configuration, various detectors were chosen between the Razor diode (IBA), the 60017 diamond (PTW), the CC01 ion chamber (IBA), the SFD diode (IBA) and EBT3 films. For circular cones, a comparison with the C-serie Novalis of another center was conducted. Results: By analyzing the measurements, the following results were high lightened: due to its large sensitive volume (2.2 mm), the diamond was found inadequate for fields smaller than 6 mm diameter. Both diodes were found in agreement but showed some discrepancies with the film due to their high Z material which virtually sharpens the penubra. The deviations observed between the two Novalis were attributed to the different positions of the jaws. Conclusion: In order to keep a unique detector for all small fields measurements, the Razor diode was selected for all energies. Disclosure: No disclosure.